Positive plate and battery
By designing non-density fluid and multi-pole ear structures on the positive electrode of the lithium-ion battery, adjusting the thickness difference of the active material layer, the battery performance degradation and safety hazards caused by the thin edge area of the lithium-ion battery are solved, and a higher level of Battery safety and performance improvements.
Patent Information
- Application Number
- CN202411386627.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-09-30
AI Technical Summary
In lithium-ion batteries with multi-pole ear structure, the edge area of the positive electrode active material layer is thinner, resulting in uneven migration of lithium ions, resulting in battery deformation, reduced capacity and rate performance, and safety hazards.
A positive electrode sheet is designed, and the current collector is divided into a first region and a second region. The first electrode is connected to the first region. The porosity of the first region is smaller than that of the second region. The thickness difference of the active material layer is adjusted by The porosity relationship meets a specific range to reduce the thickness difference between edges and intermediate regions, improve contact and battery safety.
It effectively reduces the poor contact problem between the positive electrode sheet and the diaphragm, improves the cycle life and safety of the battery, avoids lithium excretion and local overheating, and improves the overall performance of the battery.
Smart Images

Figure CN119208513A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of batteries, and in particular to a positive electrode sheet and a battery. Background Art
[0002] Lithium-ion batteries with multi-electrode lug structures have high efficiency in charge and discharge performance and are a research hotspot in the battery industry. In lithium-ion batteries with multi-electrode lug structures, the surface of the positive electrode current collector is coated with a positive electrode active material layer, and the lugs extend outward from the edge of the positive electrode current collector.
[0003] In the positive electrode sheet with a multi-pole structure, the positive electrode current collector has a thinner thickness in the edge area near the pole ear due to process reasons, resulting in a certain thickness difference between the active material layer in the edge area and other areas. If the hot pressing is not in place, the contact between the positive electrode sheet and the diaphragm will not be tight, which will hinder the normal migration of lithium ions, causing lithium ions to precipitate on the surface of the negative electrode sheet, and then cause the lithium ion battery to deform and reduce the capacity and rate performance. In addition, since the thickness of the positive electrode active material layer in the edge area is relatively thin, the current density in the edge area is significantly higher than that in other areas, and the migration speed of lithium ions in the edge area is too fast, resulting in an excessively large lithium ion concentration gradient, which in turn leads to a decrease in the electrochemical reaction rate, poor battery rate performance, and reduced cycle life; and a large amount of Joule heat will be generated in the edge area, resulting in local overheating, leading to decomposition of the electrolyte, promoting side reactions between the electrode material and the electrolyte, and even causing internal short circuits in the lithium ion battery, causing safety hazards.
[0004] Therefore, how to solve the above technical problems should be the key focus of the technology in this field. Summary of the invention
[0005] The purpose of the present application is to provide a positive electrode sheet and a battery to reduce the thickness difference between the active material layer located on the edge area of the current collector and other areas, avoid problems such as lithium plating and battery deformation, and improve the safety of the battery.
[0006] In order to solve the above technical problems, the present application provides a positive electrode sheet, comprising a non-dense current collector, a first pole ear and an active material layer located on the surface of the current collector; the current collector has pores, and the first pole ear extends outward from the current collector along a first direction;
[0007] The surface of the current collector includes a first region and a second region distributed along the first direction, the first electrode tab is connected to an edge of the first region away from the second region; the thickness of the active material layer located in the first region is less than the thickness of the active material layer located in the second region;
[0008] The first porosity of the first region is less than the second porosity of the second region, and the difference between the first porosity and the second porosity and the thickness of the active material layer in the second region satisfy the following relationship:
[0009] 5% ≤ Q% ≤ 75%;
[0010] 0.4≤H / Q≤75;
[0011] Wherein, Q%=Q2%-Q1%; Q1% is the first porosity, Q2% is the second porosity, and H is the thickness of the active material layer located in the second region in μm.
[0012] Optionally, it also includes: an auxiliary layer located on the surface of the first region, the material of the auxiliary layer includes a conductive material, the conductivity of the conductive material is greater than the conductivity of the material of the current collector, and the active material layer is located on the surface of the auxiliary layer away from the current collector.
[0013] Optionally, the material of the auxiliary layer further includes thermally conductive ceramics, and / or the conductive material is metal.
[0014] Optionally, the particle size Dv50 of the thermally conductive ceramic is in the range of 0.01 μm to 3 μm, and / or the thickness of the auxiliary layer is in the range of 0.1 μm to 5 μm.
[0015] Optionally, the relationship between the thickness of the auxiliary layer and the thickness of the active material layer located in the second region is:
[0016] 4≤H / h≤225;
[0017] Herein, h is the thickness of the auxiliary layer in μm, and H is the thickness of the active material layer located in the second region in μm.
[0018] Optionally, the relationship between the thickness of the auxiliary layer and the particle size Dv50 of the thermally conductive ceramic is:
[0019] 0.001≤a / h≤2.0;
[0020] Wherein, h is the value of the thickness of the auxiliary layer in μm, and a is the value of the particle size Dv50 of the thermal conductive ceramic in μm.
[0021] Optionally, the relationship between the difference between the first porosity and the second porosity and the particle size Dv50 of the thermally conductive ceramic is:
[0022] 0.0001≤a / Q≤0.2;
[0023] Wherein, Q% is the difference between the first porosity and the second porosity, and a is the value of the particle size Dv50 of the thermally conductive ceramic in μm.
[0024] Optionally, it also includes:
[0025] an insulating layer located on the surface of the auxiliary layer not covered by the active layer and on the surface of the active material layer in the first region,
[0026] And / or, the number of the first electrode tabs is ≥2.
[0027] Optionally, the thickness of the current collector is in the range of 4 μm to 100 μm.
[0028] and / or, the first porosity Q1% is in the range of 0<Q1%≤5%,
[0029] and / or, the second porosity Q2% is in the range of 5%≤Q2%≤75%,
[0030] And / or, a difference between a thickness of the active material layer located in the first region and a thickness of the active material layer located in the second region is in a range of 0.1 μm to 10 μm.
[0031] The present application also provides a battery, comprising any one of the above-mentioned positive electrode sheets.
[0032] A positive electrode sheet provided in the present application includes a non-dense current collector, a first pole ear and an active material layer located on the surface of the current collector; the current collector has pores, and the first pole ear extends outward from the current collector along a first direction; the surface of the current collector includes a first area and a second area distributed along the first direction, and the first pole ear is connected to an edge of a side of the first area away from the second area; the thickness of the active material layer located in the first area is less than the thickness of the active material layer located in the second area; the first porosity of the first area is less than the second porosity of the second area, and the first porosity, the second porosity and the thickness of the active material layer located in the second area satisfy the following relationship: 5%≤Q%≤75%; 0.4≤H / Q≤75; wherein, Q%=Q2%-Q1%; Q1% is the first porosity, Q2% is the second porosity, and H is the value of the thickness of the active material layer located in the second area in μm.
[0033] It can be seen that the current collector in the positive electrode sheet of the present application can be divided into a first region and a second region, the first region is located at the edge of the current collector, the first pole ear is connected to the first region, the porosity of the first region is less than the porosity of the second region, and the greater the thickness of the active material layer in the second region, the greater the porosity difference between the first region and the second region. When the active material is coated on the current collector, the active material will enter the pores. Since the second porosity on the second region is greater than the first porosity on the first region, the thickness of the active material layer on the second region becomes thinner to a greater extent, thereby reducing the thickness difference between the active material layer on the second region and the first region. During the later hot pressing, the contact between the positive electrode sheet and the diaphragm is improved to avoid lithium precipitation, battery deformation, and reduced capacity and rate performance due to poor contact.
[0034] In addition, the present application also provides a battery having the above-mentioned positive electrode sheet. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] In order to more clearly illustrate the technical solutions of the present application or the prior art, the drawings required for use in the implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0036] Figure 1 A schematic cross-sectional view of a positive electrode current collector provided in this application Figure 1 ;
[0037] Figure 2 A top view of a positive electrode current collector provided in this application Figure 1 ;
[0038] Figure 3 A schematic cross-sectional view of a positive electrode sheet provided in this application Figure 1 ;
[0039] Figure 4 A schematic cross-sectional view of a positive electrode sheet provided in this application Figure 2 ;
[0040] Figure 5 A top view of a positive electrode current collector provided in this application Figure 2 ;
[0041] Figure 6 A schematic cross-sectional view of a positive electrode current collector provided in this application Figure 2 ;
[0042] Figure 7 A schematic diagram of a battery cell structure provided in this application;
[0043] Figures 8 to 9A schematic cross-sectional view of the current collector provided in the present application before die-cutting the first electrode tab;
[0044] In the figure, 1, current collector, 2, first electrode ear, 3, active material layer, 4, recess, 5, auxiliary layer, 11, first region, 12, second region, 13, third region, 100, positive electrode sheet, 200, separator, 300, negative electrode sheet. DETAILED DESCRIPTION
[0045] In order to enable those skilled in the art to better understand the present application, the present application is further described in detail below in conjunction with the accompanying drawings and specific implementation methods. Obviously, the described implementation methods are only part of the implementation methods of the present application, rather than all of the implementation methods. Based on the implementation methods in the present application, all other implementation methods obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present application.
[0046] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0047] As mentioned in the background technology section, there is currently a certain thickness difference between the active material layer in the edge area and other areas of the positive electrode sheet. Inadequate hot pressing in the later stage will lead to poor contact with the diaphragm, which will in turn cause problems such as battery lithium deposition deformation and decreased rate performance.
[0048] In view of this, the present application provides a positive electrode sheet 100, please refer to Figures 1 to 3 ,include:
[0049] A non-dense current collector 1, a first electrode tab 2 and an active material layer 3 located on the surface of the current collector 1, the current collector 1 has pores, and the first electrode tab 2 extends outward from the current collector 1 along a first direction Y;
[0050] The surface of the current collector 1 includes a first region 11 and a second region 12 distributed along a first direction, and the first electrode tab 2 is connected to the edge of the first region 11; the thickness of the active material layer 3 located in the first region 11 is less than the thickness H of the active material layer 3 located in the second region 12;
[0051] The first porosity of the first region 11 is less than the second porosity of the second region 12, and the difference between the first porosity and the second porosity and the thickness of the active material layer in the second region satisfy the following relationship:
[0052] 5%≤Q%≤75%; (1)
[0053] 0.4≤H / Q≤75; (2)
[0054] Wherein, Q%=Q2%-Q1%; Q1% is the first porosity, Q2% is the second porosity, and H is the thickness of the active material layer located in the second region in μm.
[0055] When Q% is 5% to 75%, the difference in the collector pores at the edge and the middle area can be ensured, and part of the active material enters the collector pores, reducing the difference in the thickness of the positive electrode active material coating between the edge and the middle area; when Q% is less than 5%, there is basically no difference in the porosity between the middle and the edge, and the active material may not be able to enter the collector pores, or the amount entering is small, which does not play a role in reducing the difference in the thickness of the positive electrode active material coating between the edge and the middle area; when Q% exceeds 75%, the difference in porosity between the middle and the edge is too large, which will cause the aluminum foil collector to break during rolling. In severe cases, the positive electrode sheet will break and cannot be made into a battery cell; in less serious cases, a roll core will be made, but the electrode sheet will break during the later cycle of the battery.
[0056] When the H / Q value is 0.4-75, the operability of the process can be ensured, the thickness difference of the pole piece can be effectively eliminated, and the flattening effect of the battery can be achieved; when H / Q is greater than 75, the porosity in the middle and the edge is too small, for example: Q = 2, H = 156, H / Q = 78, at this time, the porosity difference between the middle and edge regions of the current collector is too small, which is basically the same as the conventional current collector, and the coating thickness of 150μm is too large, the thickness difference is more obvious, and the thickness difference of the active material coating in the middle and edge regions cannot be effectively reduced, and the battery becomes The bulging situation will be aggravated; when H / Q is less than 0.4, the porosity in the middle and edges is too large, for example: Q=90, H=30, H / Q=0.333, the active material coating thickness is 30μm, which is relatively thin. Although the thickness difference can be reduced, the coating surface density is small, the energy density is low, and the battery energy density is lost. If Q is too large, the aluminum foil current collector will break during rolling. In severe cases, the positive electrode sheet will break and the battery cell cannot be made. In less serious cases, a roll core can be made, but the electrode sheet will break during the later cycle of the battery.
[0057] The first direction Y is the width direction of the positive electrode sheet 100 , the second direction Z is the thickness direction of the positive electrode sheet 100 , and the third direction X is the length direction of the positive electrode sheet 100 .
[0058] The first porosity is the ratio of the volume of all pores (recesses 4) in the first region 11 to the total volume of the current collector 1 and pores within the first region 11, and can be expressed as a percentage.
[0059] The second porosity is the ratio of the volume of all pores (recesses 4) in the second region 12 to the total volume of the current collector 1 and pores within the second region 12, which can be expressed as a percentage.
[0060] The current collector 1 has two opposite surfaces in the second direction Z, and the active material layer 3 is located on one surface of the current collector 1 .
[0061] When the positive electrode sheet 100 is made into a battery cell, an active material layer 3 is provided on the side of the positive electrode sheet 100 corresponding to the negative electrode sheet, that is, when the positive electrode sheet 100 is located in the innermost layer or the outermost layer of the battery cell, the active material layer 3 is provided on one surface of the current collector 1; when the positive electrode sheet 100 is located in the middle position, active material layers 3 are provided on both surfaces of the current collector 1.
[0062] When the active material layers 3 are simultaneously located on two opposite surfaces of the current collector 1 , at both ends in the length direction, the active material layers 3 on the two opposite surfaces may be aligned at one end and staggered at the other end.
[0063] As an implementation method, the thickness of the active material layer 3 located on a single side surface of the current collector 1 can range from 10 μm to 200 μm, and the specific thickness can be determined according to the situation. For example, the thickness of the active material layer 3 located on a single side surface of the current collector 1 can be 10 μm, 50 μm, 100 μm, 150 μm, 200 μm, etc.
[0064] The number of active material layers 3 on a single surface of the current collector 1 may be one layer or two or more layers, both of which are within the protection scope of the present application.
[0065] The active material layer 3 contains a positive electrode active material, and / or a binder, and / or a conductive agent.
[0066] The positive electrode active material includes but is not limited to lithium manganese oxide, lithium cobalt oxide, lithium cobalt phosphate, lithium iron phosphate, lithium manganese phosphate, lithium vanadium phosphate, lithium-rich manganese base, nickel-cobalt-manganese ternary material, nickel-cobalt-aluminum ternary material, nickel-cobalt-manganese-aluminum quaternary material and other materials that can be used as positive electrodes, one or more mixtures; the binder includes but is not limited to polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN), polyamide (PA), polyvinyl alcohol (PVA), polyvinyl pyrrolidone (PVP), polyacrylate (PAA) and other organic binders, one or more mixtures; the conductive agent includes but is not limited to conductive carbon black, acetylene black, conductive ceramics, activated carbon, graphite, graphene, Ketjen black, polypyrrole, polyaniline and carbon nanotubes. As an embodiment, the positive electrode active material is a nickel-cobalt-manganese ternary material, the binder is polyvinylidene fluoride, and the conductive agent is acetylene black.
[0067] The thickness of the active material layer 3 located in the second region 12 can be measured by testing a thickness data every 5 mm from the boundary between the first region 11 and the second region 12, and then taking the average value as the thickness of the active material layer 3 located in the second region 12. The thickness of the active material layer 3 located in the second region 12 and the thickness of the active material layer 3 located in the first region 11 refer to the thickness of the active material layer 3 on the surface of the current collector 1, and do not include the thickness of the active material layer 3 inside the current collector 1. This technical solution can only reduce the thickness difference of the active material layer 3 on the surface of the current collector 1, and cannot reduce the total thickness difference of the active material layer 3 in the first region 11 and the second region 12.
[0068] The surface of the active material layer 3 located in the first region 11 has a certain tilt angle, and the thickness of the active material layer 3 in each part of the first region 11 is not uniform. The thickness of the active material layer 3 located in the first region 11 can be measured by testing a thickness data every 1 mm from the side of the active material layer 3 in the first region 11, and then taking the average value as the thickness of the active material layer 3 located in the first region 11.
[0069] The thickness difference between the active material layer 3 on the first region 11 and the second region 12 is the difference between the two average thickness values determined above.
[0070] The current collector 1 can be aluminum foil or the like.
[0071] The non-dense current collector 1 has a recess 4 , which penetrates the current collector 1 along the second direction Z. The first direction Y is perpendicular to the second direction Z.
[0072] The number of the recess 4 is at least one, and the specific number can be set according to the situation and is not specifically limited in this application.
[0073] The recess 4 may be made by, but is not limited to, laser etching, plasma etching, punching, photolithography, pickling, laser, anodizing, etc. The current collector 1 may also be made by 3D printing.
[0074] The shape of the recess 4 is not limited in the present application and can be set at will. For example, the recess 4 can be a through hole and / or a wire groove. The shape of the through hole includes but is not limited to a circle, a square, a rectangle, an ellipse, a triangle, a hexagon, any irregular shape or any combination thereof. The shape of the wire groove includes but is not limited to a straight groove and a curved groove.
[0075] The recesses 4 can be arranged in a regular array on the current collector 1, or in any irregular form, all within the protection scope of this embodiment.
[0076] For the through holes, any two or more through holes can be staggered and connected together, for example, the through holes can be tangentially connected together, or intersectingly connected together, etc.
[0077] In the present application, there is no limitation on the width of the recess 4 and the distance between adjacent recesses 4, which may be determined according to the actual situation.
[0078] The first pole tab 2 is electrically connected to the current collector 1, and the first pole tab 2 extends from the current collector 1 in a direction away from the current collector 1. The number of the first pole tabs 2 can be set as required, and is not specifically limited in the present application.
[0079] There are gaps between adjacent first pole tabs 2 . The gaps between adjacent first pole tabs 2 may be equal or unequal, which is not specifically limited in the present application.
[0080] The first electrode tab 2 is connected to the first region 11 , and the width L3 of the first electrode tab 2 in the first direction Y may range from 6 mm to 10 mm, and the specific width may depend on the situation. For example, the width L3 of the first electrode tab 2 may be 6 mm, 8 mm, 10 mm, etc.
[0081] The width L4 of the first region 11 may range from 2 mm to 20 mm, and the specific width may be determined according to the circumstances. For example, the width L4 of the first region 11 may be 2 mm, 4 mm, 6 mm, 8 mm, 10 mm, 14 mm, 16 mm, 18 mm, 20 mm, etc.
[0082] The width L1 of the active layer on the surface of the first region 11 may be in the range of 2 mm to 10 mm, and the specific width may be determined according to the situation. For example, the width L1 of the active layer on the surface of the first region 11 may be 2 mm, 4 mm, 6 mm, 8 mm, 10 mm, etc.
[0083] The width L2 of the second area 12 may range from 20 mm to 350 mm, and the specific width may be determined according to the situation. For example, the width L2 of the second area 12 may be 20 mm, 60 mm, 100 mm, 150 mm, 200 mm, 250 mm, 300 mm, 350 mm, etc.
[0084] The width L of the current collector 1 is equal to the sum of the widths of the first region 11 and the second region 12 , and the width L of the current collector 1 may be in the range of 20 mm to 360 mm.
[0085] When the positive electrode active material is coated on the current collector 1, the positive electrode active material can enter the recess 4, the first porosity is smaller than the second porosity, and the thickness H of the active material layer 3 on the second region 12 is thinner than that on the first region 11, thereby reducing the thickness difference between the active material layer 3 on the second region 12 and the first region 11, that is, reducing the thinning degree of the active material layer 3 on the first region 11, thereby improving the contact effect between the positive electrode sheet 100 and the components of the diaphragm during the subsequent hot pressing.
[0086] The current collector 1 in the positive electrode sheet 100 of the present application can be divided into a first region 11 and a second region 12, the first region 11 is located at the edge of the current collector 1, the first pole ear 2 is connected to the first region 11, the porosity of the first region 11 is less than the porosity of the second region 12, and the greater the thickness H of the active material layer 3 in the second region 12, the greater the porosity difference between the first region 11 and the second region 12. When the active material is coated on the current collector 1, the active material will enter the pores. Since the second porosity on the second region 12 is greater than the first porosity on the first region 11, the thickness of the active material layer 3 on the second region 12 becomes thinner to a greater extent, thereby reducing the thickness difference between the active material layer 3 on the second region 12 and the first region 11. During the later hot pressing, the contact between the positive electrode sheet 100 and the diaphragm is improved to avoid lithium precipitation, battery deformation, and reduced capacity and rate performance due to poor contact.
[0087] Please refer to Figure 4 and Figure 5 On the basis of the above-mentioned embodiments, in one embodiment of the present application, the positive electrode sheet 100 may further include: an auxiliary layer 5 located on the surface of the first region 11, the material of the auxiliary layer 5 includes a conductive material, the conductivity of the conductive material is greater than the conductivity of the material of the current collector, and the active material layer 3 is located on the surface of the auxiliary layer 5 away from the current collector 1.
[0088] The present application does not limit the type of conductive material and the conductive material can be selected at will.
[0089] The auxiliary layer 5 can be prepared by at least one of physical vapor deposition (PVD), chemical vapor deposition (CVD), electroplating, plasma spraying, pulsed laser deposition (PLD), magnetron sputtering, pulsed sputtering, sol-gel method, vacuum evaporation and the like.
[0090] The thickness of the auxiliary layer 5 in the second direction Z may range from 0.1 μm to 5 μm, and the specific thickness depends on the situation. For example, the thickness h of the auxiliary layer 5 may be 0.1 μm, 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, etc.
[0091] The width of the auxiliary layer 5 in the first direction Y is greater than or equal to the width L1 of the surface active layer of the first region 11, and less than or equal to the width L4 of the first region. The width of the auxiliary layer 5 can range from 2 mm to 20 mm, and the specific width can be set by oneself. For example, the width of the auxiliary layer 5 can be 2 mm, 6 mm, 10 mm, 15 mm, 20 mm, etc.
[0092] In the process of manufacturing the positive electrode sheet 100 , the auxiliary layer 5 is firstly manufactured on the current collector 1 , and then the positive electrode active material is coated. In the first region 11 , the active material layer 3 covers the surface of the auxiliary layer 5 which faces away from the current collector 1 .
[0093] The conductive material in the auxiliary layer 5 has better conductivity than the current collector 1, which can effectively reduce the resistance of the first region 11, guide the current to the second region 12, promote the current flow to the second region 12, reduce the current concentration in the first region 11, and avoid excessive local current causing heat.
[0094] Since the first porosity on the first region 11 of the current collector 1 is less than the second porosity on the second region 12, the area of the concave portion 4 in the first region 11 is small, and the area (path) through which the current flows is small. The area of the concave portion 4 in the second region 12 is large, and the area (path) through which the current flows is large, which will cause the current density of the first region 11 to be higher than the current density of the second region 12, and the first region 11 has a certain risk of lithium precipitation and local overheating. In this application, by providing an auxiliary layer 5 with conductivity, the current density distribution of the first region 11 can be improved, the efficiency of interfacial heat transfer can be accelerated, and the thermal management performance of the battery can be effectively improved. At the same time, the strength of the first region 11 can be improved to prevent edge deformation caused by mechanical stress or other factors, thereby ensuring the stability of the current density distribution and improving the cycle life and safety of the battery. In addition, the auxiliary layer 5 can further reduce the difference in the total coating thickness of the surface of the first region and the second region of the current collector, so that the surface of the pole piece is smoother after hot pressing, so that the fit between the first active layer and the diaphragm is better, and the problem of interfacial lithium precipitation caused by loose contact is avoided.
[0095] On the basis of the above-mentioned embodiment, in one embodiment of the present application, the material of the auxiliary layer 5 further includes thermally conductive ceramics, and / or the conductive material is metal.
[0096] In this embodiment, the metal material in the auxiliary layer 5 is not limited and can be selected at will. In one embodiment of the present application, the metal can be at least one of nickel (Ni), titanium (Ti), chromium (Cr), aluminum (Al), copper (Cu), gold (Au), silver (Ag), and platinum (Pt). Exemplarily, when the material of the current collector 1 is aluminum, the metal in the auxiliary layer 5 can be any one of copper (Cu), gold (Au), and silver (Ag) or any combination thereof.
[0097] The material of the current collector 1 is aluminum. The conductivity of silver is about 1.5 times higher than that of aluminum, the conductivity of copper is about 1.7 times higher than that of aluminum, and the conductivity of gold is about 1.4 times higher than that of aluminum.
[0098] In this embodiment, the thermally conductive ceramic material in the auxiliary layer 5 is not limited and can be selected at will. For example, the thermally conductive ceramic includes but is not limited to any one or any combination of oxide ceramics such as aluminum oxide (Al2O3), beryllium oxide (BeO), magnesium oxide (MgO) and zirconium oxide (ZrO2), or any one or any combination of nitride ceramics such as aluminum nitride (AlN) and silicon nitride (Si3N4), or any one or any combination of carbide ceramics such as silicon carbide (SiC) and tungsten carbide (WC), or any combination of oxide ceramics, nitride ceramics, and carbide ceramics.
[0099] The metal in the auxiliary layer 5 can not only improve the electronic conductivity of the positive electrode material, but also serve as a heat-conducting bridge. Its thermal conductivity can also transfer heat from the heat source to the thermally conductive ceramic, and quickly conduct the heat of the first area 11 to the second area 12 or the external environment through the thermally conductive ceramic, thereby reducing the temperature of the first area 11, avoiding local overheating, further reducing resistance, forming positive feedback, and finally achieving a more uniform current density distribution. By adding thermally conductive ceramics and making full use of the thermal conductivity advantages of both metal and thermally conductive ceramics, the heat dissipation effect of the auxiliary layer 5 can be further enhanced, the heat transfer efficiency is greatly improved, and the thermal management performance of the battery is effectively improved, thereby improving the capacity and rate performance of the battery under high temperature conditions.
[0100] On the basis of the above-mentioned embodiment, in one embodiment of the present application, the particle size Dv50 of the thermally conductive ceramic is in the range of 0.01 μm to 3 μm, and / or the thickness of the auxiliary layer 5 is in the range of 0.1 μm to 5 μm.
[0101] Generally speaking, the smaller the particle size Dv50, the higher the thermal conductivity, because the fine particles have a larger contact area, which is conducive to heat transfer. If the particles are too large, the thermal conductivity is lower, but it has good mechanical strength and stability. The particle size Dv50 of thermal conductive ceramics is preferably in the range of 0.01 to 1.5 μm to facilitate heat transfer.
[0102] Illustratively, the particle size Dv50 of the thermally conductive ceramic may be 0.01 μm, 0.05 μm, 0.1 μm, 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, etc.
[0103] If the thickness of the auxiliary layer 5 is too thick, it will increase thermal resistance, reduce heat transfer efficiency, and hinder the transmission of lithium ions from the surface of the positive electrode material to the electrolyte, reducing the battery charging and discharging efficiency; if the thickness of the auxiliary layer 5 is too thin, it is difficult to improve electronic conductivity and thermal conductivity, and the effect of improving battery performance is limited.
[0104] The thickness of the auxiliary layer 5 is preferably in the range of 0.1 μm to 2 μm. For example, the thickness of the auxiliary layer 5 can be 0.1 μm, 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, etc.
[0105] On the basis of the above-mentioned embodiment, in one embodiment of the present application, the particle size Dv50 of the thermally conductive ceramic may be in the range of greater than 0 and less than or equal to 0.2 μm, and the thickness of the auxiliary layer 5 may be in the range of 2 μm to 5 μm.
[0106] In the present application, the particle size Dv50 of the thermally conductive ceramic is relatively small, that is, the ceramic particles are relatively fine, ensuring efficient heat transfer. The thickness of the auxiliary layer 5 is relatively thick, which can provide a good heat transfer path. This combination can take into account resistance, contact area and thermal conductivity, and improve current density bearing capacity.
[0107] In other embodiments of the present application, the particle size Dv50 of the thermally conductive ceramic may be in the range of greater than or equal to 0.2 μm, and the thickness of the auxiliary layer 5 may be in the range of 0.1 μm to 2 μm.
[0108] In other embodiments of the present application, the particle size Dv50 of the thermally conductive ceramic may be in the range of 1.5 to 3 μm, and the thickness of the auxiliary layer 5 may be in the range of 2 to 5 μm.
[0109] On the basis of any of the above embodiments, in one embodiment of the present application, the relationship between the thickness of the auxiliary layer 5 and the thickness of the active material layer 3 located in the second region 12 is:
[0110] 4≤H / h≤225; (3)
[0111] Here, h is the thickness of the auxiliary layer 5 in μm, and H is the thickness of the active material layer 3 located in the second region 12 in μm.
[0112] When H / h is 4 to 225, it can ensure that the thickness of the positive electrode active material coating is constant, and the appropriate h thickness can be adjusted to better reduce the thickness difference of the positive electrode active material coating. It can also effectively connect the positive electrode material and the current collector, reduce the electron transmission resistance, and improve the battery's charge and discharge efficiency and rate performance, while playing a better role in electrical conduction, heat conduction and heat dissipation; when H / h is greater than 225, the auxiliary layer is too thin and cannot achieve good electrical conduction and heat conduction effects. Heat cannot be effectively conducted to the external environment, and heat accumulates in local areas, resulting in increased temperature rise, which in turn causes the battery to precipitate lithium and deform, and the battery performance cannot be guaranteed. When H / h is less than 4, the thickness of the positive electrode active material coating is less than the thickness of the auxiliary layer, for example, H=1.5, h=2, H / h=0.75, the thickness of the positive electrode active material coating is almost in the single digit, the coating process is more difficult, the coating process control is more difficult, and problems such as uneven coating and defects are prone to occur, which affect the battery performance and consistency. If the positive electrode active material coating is too thin, the energy density of the battery will also be lost. In addition, the thickness of the auxiliary layer will not be similar to the thickness of the positive electrode active material coating. If it is similar, the thickness of the positive electrode active material coating is too thick, which will increase the impedance, resulting in an increase in the transmission resistance of electrons from the positive electrode material to the current collector, thereby reducing the battery's charge and discharge efficiency and rate performance. If the auxiliary layer coating is too thick, it will also reduce the mechanical strength of the positive electrode material. During the charge and discharge process, due to volume expansion and contraction, the positive electrode material is easily peeled off from the current collector, and even internal short circuits may occur, causing safety accidents, and increasing costs, which is not conducive to the market competitiveness of battery products.
[0113] On the basis of any of the above embodiments, in one embodiment of the present application, in order to achieve the best thermal conductivity performance, the relationship between the thickness of the auxiliary layer 5 and the particle size Dv50 of the thermally conductive ceramic is:
[0114] 0.001≤a / h≤2.0; (4)
[0115] Here, h is the thickness of the auxiliary layer 5 in μm, and a is the particle size Dv50 of the thermally conductive ceramic in μm.
[0116] When a / h is 0.001-2.0, it can take into account the rapid transfer of electrons, improve the battery's rate performance and charge and discharge efficiency; ensure battery heat dissipation, improve the battery cycle life and safety performance; in addition, it can also ensure that it has a certain mechanical strength; when a / h is greater than 2, the diameter of the thermally conductive ceramic is greater than the thickness of the auxiliary layer, for example, a=1, h=0.2, a / h=5, the particles protrude on the surface of the auxiliary layer, which will cause the positive electrode active material coating to be lifted up, which is not conducive to reducing the coating thickness difference. In addition, if the thermally conductive ceramic particles are too large, it will increase thermal resistance and hinder heat transfer, which is not conducive to battery heat dissipation, and easily cause the internal temperature of the battery to be too high, affecting the battery cycle life and safety; if the ceramic particles are too large, it will also cause the coating structure to be unstable, which is easy to be damaged during the charge and discharge process, affecting the battery performance. When a / h is less than 0.001, for example: a=0.01, h=20, a / h=0.0005, the ceramic particles are too small, and the thickness of the auxiliary layer is relatively high. Although the ceramic particles are too small to increase the contact area, they will also increase the gaps between the particles and reduce the heat conduction efficiency. In addition, the production process becomes more difficult and is prone to generate dust, increasing safety hazards in the production process. If the ceramic particles are too small, aggregation is likely to occur during the coating process, resulting in uneven coating. Uneven coating will affect the performance of the battery, such as local differences in conductivity, which will increase the internal resistance of the battery and reduce the charging and discharging efficiency.
[0117] On the basis of any of the above embodiments, in one embodiment of the present application, the relationship between the difference Q between the first porosity and the second porosity and the particle size Dv50a of the thermally conductive ceramic is:
[0118] 0.0001≤a / Q≤0.2; (5)
[0119] Wherein, Q% is the difference between the first porosity and the second porosity, and a is the value of the particle size Dv50 of the thermal conductive ceramic in μm.
[0120] When a / Q is 0.0001-0.2, the coating thickness difference can be reduced, and suitable ceramic particles can ensure good thermal conductivity and heat dissipation, thereby improving the overall performance of the battery. When a / Q is less than 0.0001, the porosity difference is appropriate, and the particles are too small. For example, when a=0.1, Q=70, and a / Q=0.0001, it cannot achieve good electrical and thermal conductivity, and cannot effectively reduce the temperature difference between the middle and edge areas. It will still cause lithium deposition and deformation on the top of the battery. In addition, the production process becomes more difficult, and dust is easily generated, increasing safety risks in the production process. The ceramic particles are too small, and they are prone to aggregation during the coating process, resulting in uneven coating. Uneven coating will affect the performance of the battery. For example, local conductivity differences will increase the internal resistance of the battery and reduce the charging and discharging efficiency. When a / Q is greater than 0.2, for example, a=2.2, Q=1, a / Q=2.2, the porosity difference of the current collector is small, and it is almost the same as the conventional current collector without pores. The thickness difference between the coating on the edge and the middle area of the positive electrode cannot be reduced. The battery is not in place during the later formation or hot pressing. The poor contact of the components will still cause lithium deposition and deformation. In addition, if the ceramic particles are too large, it will increase the thermal resistance, hinder the transfer of heat, and is not conducive to the heat dissipation of the battery. It is easy to cause the internal temperature of the battery to be too high, affecting the battery cycle life and safety.
[0121] On the basis of any of the above embodiments, in one embodiment of the present application, the positive electrode sheet 100 may further include:
[0122] The insulating layer is located on the surface of the auxiliary layer 5 not covered by the active layer and on the surface of the active material layer in the first region,
[0123] And / or, the number of the first electrode tabs 2 is ≥2.
[0124] The insulating layer includes an insulating material, a binder, and a dispersant, wherein the insulating material may be ceramic. The ceramic includes but is not limited to any one or any combination of aluminum oxide (Al2O3), ceramic aluminum nitride (AlN), zirconium oxide (ZrO2), silicon nitride (Si3N4), silicon carbide (SiC), barium titanate (BaTiO3), strontium titanate (SrTiO3), lithium niobate (LiNbO3), lithium tantalate (LiTaO3), and lead zirconate titanate (Pb(ZrxTi1-x)O3, PZT).
[0125] The width of the insulating layer may range from 2 mm to 20 mm, preferably from 2 mm to 6 mm; the thickness of the insulating layer may range from 10 μm to 40 μm.
[0126] Illustratively, the width of the insulating layer may be 2 mm, 4 mm, 6 mm, 10 mm, 14 mm, 18 mm, 20 mm, etc., and the thickness of the insulating layer may be 10 μm, 20 μm, 30 μm, 40 μm, etc.
[0127] The insulating layer can prevent the positive electrode sheet 100 from losing powder and burrs in subsequent slitting processes, thereby avoiding the battery self-discharge problem caused by the falling powder, and preventing the powder from piercing the battery separator, reducing the battery self-discharge.
[0128] On the basis of any of the above embodiments, in one embodiment of the present application, the thickness range of the current collector 1 can be 4μm to 100μm, and / or the range of the first porosity Q1% can be 0<Q1%≤5%, and / or the range of the second porosity Q2% can be 5%≤Q2%≤75%, and / or the difference between the thickness of the active material layer 3 located in the first region 11 and the thickness of the active material layer 3 located in the second region 12 can be in the range of 0.1μm to 10μm, and / or the width range of the recess 4 can be 1μm to 10μm, and / or the spacing between adjacent recesses 4 can be in the range of 0.1μm to 5μm.
[0129] If the thickness of the current collector 1 is too thick, the volume will be relatively large, thereby resulting in a loss of energy density. If the thickness of the current collector 1 is too thin, the current collector 1 is easily broken after the recess 4 is formed.
[0130] The thickness of the current collector 1 may preferably be 5 μm to 25 μm.
[0131] For example, the thickness of the current collector 1 may be 4 μm, 5 μm, 10 μm, 20 μm, 25 μm, 30 μm, 40 μm, 50 μm, 80 μm, 100 μm, etc.
[0132] For example, the first porosity may be 0.5%, 1%, 2%, 3%, 4%, 5%, etc.
[0133] For example, the second porosity may be 5%, 10%, 20%, 40%, 60%, 70%, 75%, etc.
[0134] Exemplarily, the porosity difference may be 5%, 10%, 20%, 40%, 60%, 70%, 75%, etc., and the porosity difference is preferably between 15% and 45%.
[0135] Illustratively, the difference between the thickness of the active material layer 3 in the first region 11 and the thickness of the active material layer 3 in the second region 12 may be 0.1 μm, 1 μm, 3 μm, 5 μm, 7 μm, 9 μm, 10 μm, etc.
[0136] When the recess 4 is a through hole, the width of the recess 4 is the hole diameter; when the recess 4 is a linear groove, the width of the recess 4 is the groove diameter.
[0137] like Figure 6As shown, when the through hole exists independently and is not interlaced with other through holes, the aperture D of the through hole is 1 μm to 10 μm, preferably 1 μm to 5 μm.
[0138] For example, the aperture D of the through hole may be 1 μm, 3 μm, 5 μm, 7 μm, 9 μm, 10 μm, etc.
[0139] If the pore size D is too large, on the one hand, it is easy to cause the electrolyte to be unevenly distributed in the pores, which may affect the overall reaction efficiency of the electrode. On the other hand, it leads to poor contact between the electrode material and the current collector, affecting the effectiveness of the reaction, affecting the charge and discharge efficiency and rate performance of the battery, and also reducing the mechanical strength of the current collector 1, which is easy to deform or break during battery assembly or charge and discharge, affecting the stability and cycle life of the battery. If the pore size D is too small, it will hinder the flow of the electrolyte in the through hole, resulting in uneven distribution of the electrolyte, affecting the electrochemical performance of the battery, and it is difficult to control the porosity difference between the two regions to meet the requirements, and the effect of improving the thickness difference of the active layer between the first region and the second region cannot be achieved.
[0140] The interval d between adjacent through holes may range from 0.1 μm to 5 μm, preferably from 0.2 μm to 3 μm.
[0141] For example, the interval d between adjacent through holes may be 0.1 μm, 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, etc.
[0142] If the distance d between adjacent through holes is too large, the electrochemical activity of the porous aluminum foil will be reduced, affecting the charge and discharge efficiency and cycle life of the battery, and it will also cause uneven distribution of the electrolyte, affecting the electrochemical performance of the battery. If the distance d between adjacent through holes is too small, the stress concentration of the current collector 1 will increase, reducing the mechanical strength of the porous aluminum foil, and it is easy to deform or break during battery assembly or charge and discharge.
[0143] The present application also provides a battery cell, comprising a positive electrode sheet 100 according to any of the above embodiments, a separator 200, and a negative electrode sheet 300, wherein the positive electrode sheets 100 and the negative electrode sheets 300 are alternately stacked, and the separator 200 is located between the positive electrode sheet 100 and the negative electrode sheet.
[0144] The negative electrode sheet 300 and the separator 200 may refer to the related art and will not be described in detail here.
[0145] The battery cell can be a wound battery cell, such as Figure 7 shown.
[0146] The present application also provides a battery, comprising a second pole ear, a membrane shell and a battery cell of the above embodiment, wherein the battery cell is located in the membrane shell, and the second pole ear is connected to the first pole ear 2 in the battery cell and is partially exposed from the membrane shell.
[0147] The following is an explanation of the process of manufacturing the positive electrode sheet and forming a battery in the present application using a specific case.
[0148] (1) Preparation of coated positive electrode sheet
[0149] A target made of nickel and beryllium oxide (BeO) thermal conductive ceramic is used to sputter atoms or molecules on the surface of the target to the first region 11 on the current collector 1 by gas discharge in a vacuum environment; the third region 13 is used to die-cut the first pole ear 2, wherein the width L5 of the third region 13 can range from 6mm to 18mm. By precisely controlling the sputtering gas, time, power, and the distance between the target and the substrate, etc., the film needs to be post-processed after sputtering, such as annealing and cleaning, to control the thickness h of the auxiliary layer 5 to 4μm, the width to 6mm, and the particle size Dv50 of the beryllium oxide (BeO) thermal conductive ceramic to 0.400μm, and obtain the current collector 1 coated with the auxiliary layer 5, such as Figure 8 shown.
[0150] Before die-cutting, the width L0 of the current collector 1 is 150 mm, the sum of the width L4 of the first region 11 and the width L5 of the third region 13 is 10 mm, the width L2 of the second region 12 is 140 mm, and the thickness H1 of the current collector 1 is 10 μm.
[0151] Among them, Figure 2 As shown, the porosity difference Q of the positive electrode current collector 1 is 30%, the first porosity Q1 of the first region 11 is 0%, and the porosity Q2 of the second region 12 is 30%.
[0152] Nickel-cobalt-aluminum ternary material, acetylene black and polyvinylidene fluoride are dispersed and mixed in N-methylpyrrolidone (NMP) solvent at a ratio of 97:1.5:1.5 to obtain a positive electrode active material mixed slurry. The solid content, viscosity, coating speed and pressure of the slurry are regulated, and the positive electrode active material slurry is evenly coated on both sides of the positive electrode current collector 1 containing the auxiliary layer 5 to obtain a coated positive electrode sheet 100. The width of the positive electrode active material layer in the first region 11 is L1, which can be 5 mm, and the first region is not fully coated in the width direction. The width of the positive electrode active material layer in the second region 12 is L2, and the second region is fully coated in the width direction. The thickness H of the positive electrode active material layer 3 on one side of the second region 12 is 60 μm, as shown in FIG. Figure 8 and Fig. 9 shown.
[0153] Among them, after the positive electrode current collector 1 coated with the auxiliary layer 5 is coated with the active material coating, the surface of the auxiliary layer 5 not covered by the active layer and the surface of the active material layer in the first area are simultaneously covered with an insulating layer to prevent battery self-discharge and improve battery safety. The insulating layer has a thickness of 20 μm and a width of 6 mm.
[0154] Combination Figure 8and Fig. 9 As shown, the width L1 of the positive electrode active material layer 3 coated on the surface of the current collector 1 except the second area 12 is 5 mm, and the total thickness difference between the active material layer 3 coated on both sides of the surface of the first area 11 and the active material layer 3 coated on the second area 12, that is, the thinning thickness difference, is 6 μm.
[0155] The current collector 1 coated with the active material layer 3 is dried to obtain a coated positive electrode sheet 100. Due to the presence of the second porosity Q2 in the second region 12 of the current collector 1, part of the active material enters into the recess 4 thereof during the coating process, and the difference in thickness H between the active material layer 3 on the surface of the second region 12 and the active material layer 3 on the surface of the first region 11 is reduced. The auxiliary layer 5 of the first region 11 further reduces the difference in thickness H between the active material layer 3 on the surface of the second region 12 and the active material layer 3 on the surface of the first region 11.
[0156] (2) Preparation of die-cut positive electrode sheet 100
[0157] The coated positive electrode sheet 100 obtained in step (1) is subjected to roller pressing to obtain a rolled positive electrode sheet 100. Roll pressing refers to the process of compacting the coated electrode sheet to make the surface of the electrode sheet smoother and flatter, thereby improving the adhesion of the active material, preventing the electrode sheet from falling off during the cycle, and improving the energy density of the battery.
[0158] During the rolling stage, after the positive electrode sheet 100 is pressed, the active material and the current collector 1 are in closer contact, which reduces the resistance and polarization, and improves the battery power density and cycle life; the positive electrode sheet 100 is flatter, which can effectively ensure the hot pressing effect of the battery cell during the formation stage, avoid the problem of lithium deposition and battery deformation caused by poor contact of the first edge area 11, and ensure the uniformity of the edge current density distribution, accelerate the heat transfer rate, avoid the occurrence of side reactions, and improve the electrochemical performance of the battery;
[0159] The rolled positive electrode sheet 100 is die-cut to obtain a positive electrode sheet 100 having 26 first tabs 2. Figure 5 As shown, the width L of the positive electrode sheet 100 after die cutting is L1+L4, which is 146 μm.
[0160] (3) Preparation of lithium-ion batteries
[0161] The die-cut positive electrode sheet 100 obtained in step (2) is wound with the negative electrode sheet and the separator to obtain a bare core, which is then welded, packaged, sprayed and baked to obtain a dry core, and then an electrolyte (containing 1 mol / L LiTFSI solute, a uniform solution of DEC:EC:DMC mixed in a solvent volume ratio of 1:1:1) is injected, and the battery after injection is formed, sealed and sorted, and then the electrical performance is tested.
[0162] The positive electrode sheet and battery provided in the present application are further described below in conjunction with embodiments.
[0163] In the following embodiments, the performance of the lithium-ion battery is tested according to the following method:
[0164] (1) Capacity retention rate:
[0165] The battery was charged to 4.25V at 1.5C, and discharged to 2.0V at 3.0C. The initial capacity value C0 and the capacity value after n cycles were recorded. The capacity retention rate was calculated according to the following formula:
[0166] Capacity retention rate = (nth cycle capacity value Cn / initial capacity value C0)*100%;
[0167] (2) Thickness expansion rate:
[0168] The battery was charged to 4.25V at 1.5C and discharged to 2.0V at 3.0C. The initial thickness of the battery and the thickness after n cycles were recorded using a PPG thickness gauge. The expansion rate was calculated using the following formula:
[0169] Expansion rate Wn = (nth cycle thickness value Hn-initial thickness value H0) / initial thickness value H0*100%;
[0170] (3) Appearance of battery after 300 cycles:
[0171] Observe the battery surface with the naked eye to see if there are obvious bulges, pitting, ridges, bulging, foreign matter, corners, corrosion, deformation, scratches, dents, cracks, bubbles, discoloration and other defects. Touch the battery with your fingers to see if it feels good. Confirm the type of abnormal appearance of the battery. If it is difficult to judge with the naked eye, use a microscope or magnifying glass to assist.
[0172] Determine the type of battery bulge based on the location of the bulge and whether it can be felt, for example, head bulge, body (middle) bulge, bottom bulge;
[0173] Based on the location of the battery ridges or warping and whether there is a feel, determine what type of ridge the battery has, for example, side ridges, main body (middle) ridges, or bottom warping.
[0174] (4) Top interface of the battery cell after 300 cycles
[0175] Disassemble the battery in an environment with a temperature of 20±5℃, relative humidity <10%RH, and dew point ≤-20℃. The specific steps are as follows:
[0176] Prepare the fully charged cycled battery that needs to be dissected, confirm whether there are any abnormalities in the appearance of the front and back of the battery cell, and take photos to record; remove the aluminum-plastic film, take out the internal roll core, check whether there are any abnormalities in the appearance of the front and back and the top and bottom, and take photos to record; remove the ending tape, unfold the roll core, separate the positive electrode from the diaphragm, separate the negative electrode from the diaphragm, check whether there are any abnormalities on the front and back of the positive electrode, negative electrode and diaphragm, and focus on confirming whether there are black spots on the top of the negative electrode sheet to indicate lithium precipitation, and take photos to record.
[0177] (5) Temperature rise of the battery cell
[0178] Use glue to fix the temperature-sensing wire in the middle of the battery body surface, collect the initial temperature of the battery and the temperature during the cycle, and calculate the difference between the cycle 300T and the initial temperature.
[0179] (6) Test method for temperature rise in the edge area of the battery cell
[0180] Use glue to fix the temperature sensing wire in the middle of the top area of the battery, collect the initial temperature of the battery and the temperature during the cycle, and calculate the difference between the cycle 300T and the initial temperature
[0181] Examples 1 to 7, Comparative Examples 1 to 3
[0182] Provide as Figure 8 The current collector 1 shown has a width L of 150 mm and a thickness of 10 μm. The surface of the current collector 1 includes a third region 13, a first region 11 and a second region 12 distributed along a first direction. The width L5 of the third region 13 is 4 μm, the width L4 of the first region 11 is 6 mm, the width L2 of the second region 12 is 140 mm, and the porosity Q1% of the first region 11 and the porosity Q2% of the second region 12 are shown in Table 1.
[0183] A target made of nickel and beryllium oxide (BeO) thermal conductive ceramic with a particle size Dv50 of aμm (see Table 1 for details) (mass ratio of 12:1) is sputtered onto the surfaces of both sides of the first region 11 of the current collector by gas discharge in a vacuum environment, and an auxiliary layer 5 is formed after annealing and cleaning. The auxiliary layer 5 has a thickness of hμm (see Table 1 for details) and a width of 6mm, that is, the first region 11 is fully coated in the width direction;
[0184] The nickel-cobalt-aluminum ternary material NCA, acetylene black and polyvinylidene fluoride are dispersed and mixed in an N-methylpyrrolidone (NMP) solvent in a ratio of 97:1.5:1.5 to obtain a positive electrode active material mixed slurry, and the solid content, viscosity, coating speed and pressure of the slurry are adjusted to uniformly coat the positive electrode active material slurry on both sides of the first region 11 and the second region 12 of the current collector 1, wherein the positive electrode active material slurry is coated on the second region 12 in the width direction, and the coating width L1 in the first region 11 in the width direction is 5 mm, and the uncoated portion is located on the side away from the second region 12. After drying, rolling, slitting and die-cutting the coating, a positive electrode sheet is obtained. The thickness of the positive electrode active material layer on the surface of the second region 12 in the positive electrode sheet is shown in Table 1.
[0185] The negative electrode graphite, carbon nanotubes, and binder are dispersed and mixed in a solvent water in a certain ratio of 97:1.2:1.8 to obtain a negative electrode active material mixed slurry, and the above slurry is coated on the copper foil, and the coating is dried, rolled, slit and die-cut to obtain the negative electrode pole piece. The positive electrode pole piece, the separator and the negative electrode pole piece are wound to obtain a bare coil core, and a dry coil core is obtained after welding, packaging, coding and baking, and then an electrolyte (containing 1 mol / L LiTFSI solute, a uniform solution of DEC:EC:DMC mixed in a solvent volume ratio of 1:1:1) is injected, and the battery after injection is formed, sealed and sorted to obtain a lithium-ion battery.
[0186] The lithium-ion battery was tested according to the method described above, and the results are shown in Table 2.
[0187] Table 1
[0188] Q1 Q2 H H / Q a h H / h a / h a / Q Example 1 0 75 30 0.4 0.4 4 7.5 0.1 0.0053 Example 2 0 30 30 1 0.4 4 7.5 0.1 0.0133 Example 3 0 30 60 2 0.4 4 15 0.1 0.0133 Example 4 0 12 60 5 0.4 4 15 0.1 0.0333 Example 5 2 7 50 10 0.4 4 12.5 0.1 0.0800 Example 6 5 7 100 50 0.4 4 25 0.1 0.2000 Example 7 5 7 150 75 0.4 4 37.5 0.1 0.2000 Comparative Example 1 0 50 15 0.3 0.4 4 3.75 0.1 0.0080 Comparative Example 2 0 1 80 80 0.4 4 20 0.1 0.4000 Comparative Example 3 5 6 80 80 0.4 4 20 0.1 0.4000
[0189] Table 2
[0190]
[0191] It can be seen from Table 1 and Table 2 that when H / Q is 0.4-75, the operability of the process can be ensured, the thickness difference of the pole piece can be effectively eliminated, and the flattening effect of the battery can be achieved. When H / Q is less than 0.4 (Comparative Example 1) or greater than 75 (Comparative Example 3), the flattening effect of the battery cannot be guaranteed; when H / Q is greater than 75 and Q2 is too small (Comparative Example 2), not only the flattening effect of the battery cannot be guaranteed, but also the cycle performance of the battery will be significantly reduced, and the expansion rate will be significantly increased.
[0192] Examples 9 to 15, Comparative Examples 4 to 8
[0193] The difference from Example 3 is that the thickness of the auxiliary layer is different. The thickness of the auxiliary layer h μm is shown in Table 3, and the obtained battery performance test results are shown in Table 4.
[0194] In Example 8, the thickness Hμm of the active material layer is adjusted to 20μm, and the particle size Dv50 of the thermal conductive ceramic is adjusted to 0.02μm;
[0195] Example 13: The thickness H μm of the active material layer is adjusted to 20 μm at the same time;
[0196] Comparative Example 6: The thickness H μm of the active material layer is adjusted to 20 μm;
[0197] Table 3
[0198] project h H / h a / h Comparative Example 4 0.00 / / Example 8 0.10 200 2.00 Example 9 0.50 120 0.80 Example 10 2.00 30 0.20 Embodiment 11 3.00 20 0.13 Example 12 5.00 12 0.08 Example 13 5.00 4 0.08 Embodiment 14 4.00 15 0.10 Embodiment 15 3.75 225 0.11 Comparative Example 5 3.92 235 0.10 Comparative Example 6 5.00 0.4 0.08 Comparative Example 7 4.00 240 0.10 Comparative Example 8 6.00 10 0.07 Table 4
[0199]
[0200] It can be seen from Table 3 and Table 4 that the thickness of the auxiliary layer within 0.1 μm to 5 μm can ensure the electrical performance of the battery. The thickness less than 0.1 μm (Comparative Example 4) or the thickness greater than 5 μm (Comparative Example 8) not only affects the electrical performance of the battery, but also affects the flatness and expansion rate of the battery.
[0201] When H / h is 4-225, it can ensure that the battery has high charge and discharge efficiency and rate performance while having good appearance flatness and low expansion rate. When H / h is less than 4 (Comparative Example 6) or greater than 225 (Comparative Examples 5 and 7), the electrical performance and flatness performance of the battery will be greatly affected.
[0202] Examples 16 to 22, Comparative Examples 9 to 12
[0203] The difference from Example 3 is that the particle size Dv50 of the thermally conductive ceramic used is different. The particle size Dv50aμm of the thermally conductive ceramic is shown in Table 5, and the battery performance test results are shown in Table 6.
[0204] In Example 19, the thickness hμm of the auxiliary layer is adjusted to 1.5μm;
[0205] Comparative Example 10: The thickness hμm of the auxiliary layer is adjusted to 1.5μm;
[0206] Comparative Example 11: The porosity Q1% of the first region is adjusted to 5%, the porosity Q2% of the second region is adjusted to 7.5%, and the particle size Dv50aμm of the thermally conductive ceramic is adjusted to 2 microns;
[0207] Comparative Example 12: The porosity Q1% of the first region is adjusted to 5%, the porosity Q2% of the second region is adjusted to 7%, and the particle size Dv50aμm of the thermally conductive ceramic is adjusted to 3 microns;
[0208] Table 5
[0209] project a a / h a / Q Comparative Example 9 0.002 0.0005 0.0001 Example 16 0.01 0.0025 0.0003 Embodiment 17 0.4 0.1 0.013 Embodiment 18 2 0.5 0.067 Embodiment 19 3 2 0.100 Comparative Example 10 2 3 0.067 Embodiment 20 0.03 0.0075 0.001 Embodiment 21 0.39 0.0975 0.013 Embodiment 22 2 0.5 0.2 Embodiment 23 0.2 0.05 0.0003 Comparative Example 11 2 0.5 0.8 Comparative Example 12 3 0.75 1
[0210] Table 6
[0211]
[0212] It can be seen from Table 5 and Table 6 that when a / h is 0.001 to 2.0, the electrical performance of the battery can be guaranteed. When a / h is less than 0.001 (Comparative Example 9) or greater than 2 (Comparative Example 10), it not only affects the electrical performance of the battery, but also affects the flatness and expansion rate of the battery.
[0213] When a / Q is 0.0001 to 0.2, the electrical performance of the battery can be guaranteed. When it is greater than 0.2 (Comparative Examples 11 and 12), it not only affects the electrical performance of the battery, but also affects the flatness and expansion rate of the battery.
[0214] Examples 25-27, Comparative Examples 12-13
[0215] The difference from Example 3 is that the porosity of the current collector 1 used is different. The porosity-related parameters of the current collector are shown in Table 7, and the battery performance test is shown in Table 8.
[0216] Table 7
[0217] project Q1 Q2 Q H / Q a / Q Comparative Example 12 0 3 3 20 0.133 Embodiment 25 5 20 15 4 0.027 Embodiment 26 0 45 45 1 0.009 Embodiment 27 0 60 60 1 0.007 Comparative Example 13 0 80 80 0.75 0.005
[0218] Table 8
[0219]
[0220] It can be seen from Tables 7 and 8 that when Q% is 5% to 75%, the battery can be guaranteed to have good electrical properties and a smooth appearance. When Q% is less than 5% (Comparative Example 12), the battery's electrical properties and appearance cannot be guaranteed. When Q% is greater than 75% (Comparative Example 13), not only can the battery's electrical properties not be maintained, but the positive electrode sheet may break although there is no obvious abnormality in the appearance.
[0221] In this specification, various embodiments are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the various embodiments can be referenced to each other.
[0222] The above is a detailed introduction to the positive electrode sheet and battery provided by the present application. Specific examples are used herein to illustrate the principles and implementation methods of the present application. The above description of the implementation methods is only used to help understand the scheme and core ideas of the present application. It should be pointed out that for ordinary technicians in this technical field, without departing from the principles of the present application, several improvements and modifications can be made to the present application, and these improvements and modifications also fall within the scope of protection of the present application.
Claims
1. A positive electrode sheet, characterized in that: It includes a non-dense current collector, a first electrode tab and an active material layer located on the surface of the current collector; The current collector has pores, and the first electrode tab extends outward from the current collector along a first direction; The surface of the current collector includes a first region and a second region distributed along the first direction, the first electrode tab is connected to an edge of the first region away from the second region; the thickness of the active material layer located in the first region is less than the thickness of the active material layer located in the second region; The first porosity of the first region is less than the second porosity of the second region, and the difference between the first porosity and the second porosity and the thickness of the active material layer in the second region satisfy the following relationship: 5%≤Q%≤75%; 0.4≤H / Q≤75; Wherein, Q%=Q2%-Q1%; Q1% is the first porosity, Q2% is the second porosity, and H is the thickness of the active material layer located in the second region in μm.
2. The positive electrode sheet according to claim 1, characterized in that: Also includes: An auxiliary layer is located on the surface of the first region, the material of the auxiliary layer includes a conductive material, the conductivity of the conductive material is greater than the conductivity of the material of the current collector, and the active material layer is located on the surface of the auxiliary layer away from the current collector.
3. The positive electrode sheet according to claim 2, characterized in that: The material of the auxiliary layer further includes thermally conductive ceramics, and / or the conductive material is metal.
4. The positive electrode sheet according to claim 3, characterized in that: The particle size Dv50 of the thermally conductive ceramic is in the range of 0.01 μm to 3 μm, and / or the thickness of the auxiliary layer is in the range of 0.1 μm to 5 μm.
5. The positive electrode sheet according to claim 2, characterized in that: The relationship between the thickness of the auxiliary layer and the thickness of the active material layer located in the second region is: 4≤H / h≤225; Herein, h is the thickness of the auxiliary layer in μm.
6. The positive electrode sheet according to claim 4, characterized in that: The relationship between the thickness of the auxiliary layer and the particle size Dv50 of the thermally conductive ceramic is: 0.001≤a / h≤2.0; Wherein, a is the value of the particle size Dv50 of the thermally conductive ceramic in μm.
7. The positive electrode sheet according to claim 3, characterized in that: The relationship between the difference between the first porosity and the second porosity and the particle size Dv50 of the thermally conductive ceramic is: 0.0001≤a / Q≤0.2; Wherein, a is the value of the particle size Dv50 of the thermally conductive ceramic in μm.
8. The positive electrode sheet according to claim 2, characterized in that: Also includes: an insulating layer located on the surface of the auxiliary layer not covered by the active layer and on the surface of the active material layer in the first region, And / or, the number of the first electrode tabs is ≥2.
9. The positive electrode sheet according to claim 1, characterized in that: The thickness of the current collector is in the range of 4 μm to 100 μm. and / or, the first porosity Q1% is in the range of 0<Q1%≤5%, and / or, the second porosity Q2% is in the range of 5%≤Q2%≤75%, And / or, a difference between a thickness of the active material layer located in the first region and a thickness of the active material layer located in the second region is in a range of 0.1 μm to 10 μm.
10. A battery, characterized in that: Comprising the positive electrode sheet as described in any one of claims 1 to 9.
Citation Information
Patent Citations
Electrode plate, battery, battery pack and electric equipment
CN116314591A
Current collector, electrode plate and battery
CN215220764U
Positive plate and battery
CN218039279U
Electrode plate and battery
CN218957773U
KR20230082580A
Cited By
Positive pole piece, secondary battery and electronic device
CN121416424A
